Relationship between the Van Kleeck and mass-balance calculation of volatile solids loss - Switzenbaum, Michael S (Water environment research : a research publication of the Water Environment Federation, 2003)
An equation was developed that quantifies the relationship between volatile solids reduction (VSR) calculated by the Van Kleeck and mass-balance equations. Two sets of data were used to illustrate the significance of fixed-solids loss on the agreement between the two methods. The Van Kleeck equation assumes that fixed solids are conserved during the digestion process; however, this assumption is not needed for the mass-balance equation. Therefore, if substantial changes in the fixed-solids concentration occur, the Van Kleeck equation will not be as accurate as the mass-balance equation for computing VSR and will also underestimate VSR